COMODIFICATION OF NGABEN GOTONG ROYONG (MUTUALLY PERFORMED CREMATION CEREMONY) AT GERYA TAMAN SARI LINGGA BANYUASRI SUBDISTRICT, BULELENG REGENCY - Nyoman Kebayantini, Ni Luh; Ardika, I Wayan; Semadi Astra, I Gde; Mariyah, Emiliana (E-Journal of Cultural Studies; Vol. 5, No. 1 Januari 2011)
Cremation ceremony is a ritual performed by Bali-Hindu followers when someone dies. Itis classified as a big ceremony for the reason that it costs much money, labor and time. Ascommunity members, the Bali Hindu followers are faced with so many problems that manycannot perform cremation ceremony conventionally. As a response to this condition, thesulinggih (priest) residing at Gerya Tamansari Lingga (Griya = a particular residence where thepriest resides) has planned to produce the mutually-performed cremation ceremony. Basically, itis a practice of comodified cremation ceremony which is offered to be cheap, practical and to beeasily performed.It is produced to obtain a profit. Therefore, every material and manpower involved arecommodities which have exchange values. As far as its production process is concerned, theconsumers and the object are made not to be related. The habitus, that is, the belief of Bali-Hindufollowers that a cremation ceremony should be performed when someone dies, the cultural andsymbolic capitals in the forms of knowledge, status, and authority and the legitimacy of thepriest residing at Gerya Taman Sari Lingga, and the domain that they are not able to perform theconventional ceremony have led to the performance of the mutually-performed cremationceremony. It has various meanings such as the meaning of intensification of religious values, themeaning of tradition degradation, the meaning of egalitarian, the meaning of efficiency, themeaning of welfare, the aesthetic meaning and the meaning of image.
Keywords: comodification, mutually-performed cremation ceremony, gerya (a particular place where the priest resides), sulinggih (the priest).